rbc L sequences reveal multiple cryptic introductions of the Japanese red alga Polysiphonia harveyi - Lynne McIvor; Christine A. Maggs; Jim Provan; Michael J. Stanhope (Molecular Ecology, 2001)
In Europe, the last 20 years have seen a spectacular increase in accidental introductions of marine species, but it has recently been suggested that both the actual number of invaders and their impacts have been seriously underestimated because of the prevalence of sibling species in marine habitats. The red alga Polysiphonia harveyi is regarded as an alien in the British Isles and Atlantic Europe, having appeared in various locations there during the past 170 years. Similar or conspecific populations are known from Atlantic North America and Japan. To choose between three competing hypotheses concerning the origin of P. harveyi in Europe, we employed rbc L sequence analysis in conjunction with karyological and interbreeding data for samples and isolates of P. harveyi and various congeners from the Pacific and North Atlantic Oceans. All cultured isolates of P. harveyi were completely interfertile, and there was no evidence of polyploidy or aneuploidy. Thus, this biological species is both morphologically and genetically variable: intraspecific rbc L divergences of up to 2.1% are high even for red algae. Seven rbc L haplotypes were identified. The four most divergent haplotypes were observed in Japanese samples from Hokkaido and south‐central Honshu, which are linked by hypothetical ‘missing’ haplotypes that may be located in northern Honshu. These data are consistent with Japan being the centre of diversity and origin for P. harveyi . Two non‐Japanese lineages were linked to Hokkaido and Honshu, respectively. A single haplotype was found in all North Atlantic and Mediterranean accessions, except for North Carolina, where the haplotype found was the same as that invading in New Zealand and California. The introduction of P. harveyi into New Zealand has gone unnoticed because P. strictissima is a morphologically indistinguishable native sibling species. The sequence divergence between them is 4–5%, greater than between some morphologically distinct red algal species. Two different types of cryptic invasions of P. harveyi have therefore occurred. In addition to its introduction as a cryptic sibling species in New Zealand, P. harveyi has been introduced at least twice into the North Atlantic from presumed different source populations. These two introductions are genetically and probably also physiologically divergent but completely interfertile.